PENGENALAN DAN PEMBIASAAAN PERILAKU HIDUP SEHAT DAN BERSIH SEJAK DINI PADA SISWA SEKOLAH DASAR - Hukama, La Adhan; Razih, Muhammad; R, Rayhan Aneflin; R, Virjinea Hawani; Az-Zahra, Venezia; Fadlilah, Aldhaf; Larasati, Dinda Kania; Budi, Amanda Salsabila Audia; Mulya, Alzalisa Ridha; Lestari, Nabila Ayu; Aprilia, Nadia (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Kristen Wira Wacana Sumba, 2024)
Sustainable Development Goals (SDGs) is a global and national agreement that aims to improve the welfare of society. One of the goals of the SDGs is a Healthy and Prosperous Life. In order to support the acceleration of the achievement of the SDGs, YARSI University organizes Real Work Lecture (KKN) activities with the theme